Colina do Horto geosite: possibilities of geographical education - Sousa, Sinara Gomes de; Gomes Lopes, Antônia Janaína (Revista Ensino de Geografia (Recife), 2021)
The present work has as main objective to analyze and explore the potential that the space of the Colina do Horto geosite has for the development of practices that base the geographic education, in the light of the concept of landscape. In this way, we sought to discuss the physical-natural aspects of local and regional and social geodiversity, such as faith, religiosity, and the symbols that characterize the researched area, also highlighting its historical role in the production of space. From this, a theoretical discussion of the concept of landscape was made in different approaches, whether as a functional (geosystem) and symbolic system (FURLAN, 2019) and how these approaches can be used in the teaching of geography and for the construction of geographic education. Finally, the relationship between the geosite landscape (as a natural system and symbolic system) - in its multiple facets and temporalities - with geographic education was established, pointing out methodological proposals for its development